On trans at high school: Bodies, discourses and gazes. Some reflections on the Costa Rican context - Fernández, Daniel Fernández (Education Policy Analysis Archives, 2021)
This paper develops an analysis of the discursive formations of teachers and high school students belonging to the Costa Rican educational system regarding to the presence of transgender people in school. In theoretical level, the article deals with the postulates of the queer theory, as a way to analyze the complexities involved in the construction of trans identity, without therefore ascribing to a univocal model of interpretation of gender and sexuality. In terms of methodology, the research that gives rise to the present text was approached from a qualitative standpoint. With regard to the field work, semi-structured interviews were conducted, and regarding the analysis of the information, a Foucaultian discursive analysis was carried out. The analysis shows that male-female sexual binarism and the fixity of gender roles continue to have a considerable impact on how the trans body is viewed in the school's biopolitical setting.